Cover Crops and Nematicides for Sting Nematode Management - Duncan, Larry; Desaeger, Johan; Wu, Sheng-Yen (EDIS, 2020)
The citrus row middle habitat changed profoundly beginning in the 1970s as mowing replaced disking for weed management. This change ended the costly cycle of cutting and regrowing citrus roots near the soil surface and reduced soil erosion, among other benefits. Mowing also allowed a seasonal succession of native plants to flourish, providing a more stable and diverse habitat for both beneficial and harmful organisms.